Implementation of STEAM in Science Learning: A Systematic Literature Review - Arfilia Wijayanti; Wiyanto Wiyanto; Saiful Ridlo; Parmin Parmin (International Conference on Science, Education, and Technology, 2022)
The development of science and technology is growing rapidly in the 21st century. The development of science and technology is needed to support human resources to produce quality education. Integrated learning is important to improve student learning outcomes. This research was conducted by analyzing data from articles to find out: 1) the objectives, methods, and results of research on the implementation of STEAM (Science, Technology, Engineering, Art, and Mathematics), 2) the application of science concepts and the level of education in the implementation of STEAM, and 3) the integration of learning models/media in the implementation STEAM in science learning. A systematic literature review articles using the Prisma design in the 2015-2020 period in the Scopus and Google scholar databases found 11 articles related to the implementation of STEAM in science learning that met the criteria. The results showed that there were three categories of research objectives in the implementation of STEAM, the experimental method was the most widely used and all research results showed learning outcomes in accordance with the research objectives. The application of concepts in the implementation of STEAM in science learning is divided into fields of science such as physics, chemistry, and biology. Senior high schools dominate the implementation of STEAM in science learning, followed by junior high schools and elementary schools. In addition, the implementation of STEAM can also be integrated with various models, modules and learning media. Next, STEAM learning can be designed for prospective elementary school teacher students to gain experience for learning in the classroom later.